Information-sensitive leviathans - Andreas Nicklisch; Kristoffel Grechenig; Christian Thoeni (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
We study information conditions under which individuals are willing to delegate their sanctioning power to a central authority. We design a public goods game in which players can move between institutional environments, and we vary the observability of others' contributions. We find that the relative popularity of centralized sanctioning crucially depends on the interaction between the observability of the cooperation of others and the absence of punishment targeted at cooperative individuals. While central institutions do not outperform decentralized sanctions under perfect information, large parts of the population are attracted by central institutions that rarely punish cooperative individuals in environments with limited observability.
Keywords: C92; D02; H41; 330; centralized sanctions; cooperation; experiment; endogenous institutions